Evaluación de la promoción de la salud bucal para motivar a niños de 6 a 8 años que cursan la educación básica en el Centro Educativo Isaac Newton - Flores Jara, María Gabriela (2014)
Currently the importance given to the Promotion of Oral Health needs to be evaluated in relation to the impact that it generates in the population receiving the promotion. Therefore, a study of educational group intervention took place in a universe of 80 children between 6-8 years of age, who were randomly divided into a Control Group and an Experimental Group. Objectives: The main purpose of this research is to evaluate the effectiveness of a program for the Promotion of Oral Health as a teaching method, with a puppet show and a Manual for the Promotion of Oral Health. Materials and Methods: The research was carried out at the Centro Educativo Isaac Newton Education located in Quito - Ecuador, with students attending in the period from September to July of 2013, prior informed consent, a clinical diagnosis was made by the Simplified Index of Oral Hygiene, and the oral health knowledge through a CAP survey before and after the intervention, which provided two diagnostic measurements separated between them with a period of one month. Results: Once the data collected, and analyzed, indicated that the IHO - S at baseline, showed that 15% of participants were categorized in the Good Hygiene Group, however, in the second measurement this value increased to 71, 25 %. Also showed positive changes in relation to the frequency of teeth brushing, the same as those expressed in the survey. The analysis with a T Student test established that there is a statistically significant change (p same 0.016) in the Oral Health of participants after applying the Promotion of Oral Health program. Conclusions: It is necessary to implement and update educational programs focused on Oral Health in scholars because it is a medium capable of improving their quality of life and change their hygiene habits.